Current insights in the molecular genetic pathogenesis of amyotrophic lateral sclerosis - Zhou, Wan; Xu, Renshi (Frontiers in Neuroscience, 2023)
Amyotrophic lateral sclerosis (ALS) is a progressive and fatal neurodegenerative disease that leads to the massive loss of motor neurons in cerebrum, brain stem and spinal cord. It affects not only motor neurons but also other neurons and glial cells, resulting in the progressive muscle atrophy, the severe disability and the eventual death due to the respiratory failure. The pathogenesis of ALS is not fully understood. Currently, several factors are considered to be involved in the pathogenesis of ALS, such as genetic factors, imbalances in protein homeostasis, RNA metabolism disorders, mitochondrial dysfunctions, glutamate-mediated excitatory toxicities and intra-neuronal material transport disorders in neurons. The study of genetic mutations related to ALS pathogenesis will link the molecular and cellular mechanisms of the disease, thus enhancing the understanding of its occurrence and progression, thereby providing new insights for the pathogenesis of ALS. This review summarizes the current insights in the molecular genetic pathogenesis of ALS.